Movimentos sociais religiosos e políticas públicas: entre a letra do Estado e a ação política dos afrorreligiosos. - Nunes, Edson de Araújo (2018)
We articulate the interdisciplinary lenses of the Sciences of Religion to analyze the constitution of public policies focused on Afro-brazilian religions. Considering the Secular State, according to the Brazilian Constitution of 1988, the actions of terreiros have, as a flag, the historical struggle, the respect to ritual practices and the protection of their sacred temples and liturgies. From the formulation and application of public policies, meeting the demands of afro-religious in the context of creation of Secretary of Policies for the Promotion of Racial Equality (Secretaria de Políticas de Promoção da Igualdade Racial - SEPPIR), we see a historical break on this problem: relationship State x Afro-brazilian religions. Methodologically, our research is qualitative and guided by documentary, bibliographic and field research. We also conducted interviews with representatives from the State and from civil society, especially in the metropolitan region of Recife. After analyzing a decade of SEPPIR reports, we observe public actions in the communities of African matrix and confront official data of the State organisms with the life experiences of the militant devotees, which form what we call religious social movements, we can say that the process of Racial Equality Public Policies for terreiros has not been consolidated and is also undergoing a violent dismantling whose roots lie in the political, economic and social crisis established with the parliamentary coup of 2016.